Measuring consumer effort in circular economy initiatives in the food domain: An exploratory analysis. Issue 2 (February 2023) - Paparella, A.; Vecchio, R.; Cembalo, L.; Lombardi, A.
Abstract: The transition towards a Circular Economy (CE) system requires a change in consumers' behavioural pattern that implies a certain level of effort which, in turn, could affect initiatives' success. Although consumers' role in CE is increasingly drawing the attention of scholars, limited knowledge is available on the evaluation of consumer's effort in CE initiatives. The current research provides an identification and measurement of the core parameters affecting consumer effort, offering a comprehensive Effort Index applied to 20 CE companies operating in food domain. Companies were classified in 5 categories (Quantity of food, Appearance of food, Edibility of food, Living with food and Local and sustainable food); the analysis of the companies revealed 14 parameters building the Effort Index. Results showed that initiatives ascribable to the category "Local and sustainable food" require higher levels of consumer effort; in contrast, case studies belonging to "Edibility of food" group are less effort-requiring.